APPLICATION OF THE GPS/EGNOS SOLUTION FOR THE PRECISE POSITIONING OF AN AIRCRAFT VEHICLE - Kamil KRASUSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The results of research concerning the implementation of the GNSS technique in the area of air navigation are presented in this article. In particular, a research test was conducted for the purposes of checking the functioning of a satellite-based augmentation system (SBAS) to assist with air navigation. Ultimately, analyses of the parameters of accuracy, availability, continuity and integrity with the procedure when landing aircraft with an SBAS APV-I landing were conducted. The navigation and observation data of the GPS system and differential European Geostationary Navigation Overlay Service (EGNOS) corrections were used in the research test. The navigation and observation data of the GPS system in the RINEX format were registered through the Topcon Hiper Pro receiver placed in the cabin of pilots in the Cessna 172 aircraft during a flight experiment conducted in Dęblin in 2010. The coordinates of the Cessna 172 aircraft in the ellipsoid BLh frame were reconstructed by using the solution offered by the single point positioning (SPP) method in the RTKLIB program. The accuracy when setting coordinates of the aircraft is higher than 2.4 m in the horizontal plane and better than 4 m in the vertical plane. The integrity of the satellite positioning is higher than 15 m in the horizontal plane and better than 21.1 m in the vertical plane. The availability of the constellation of GPS/EGNOS satellites equalled 100% during the flight experiment, which confirms that the loss of continuity when determining the position of the aircraft did not occur. The parameters of the accuracy and the integrity with International Civil Aviation Organization (ICAO) technical standards were compared in this article. The results of the conducted test shows that the presented research methods can be applied in the precise positioning of the aircraft when using the GPS/EGNOS solution for air navigation.